Trichoderma orarium (Hypocreales): a new species from Taiwan - Wei, Yu-Hui; Liou, Guey-Yuh; Tzean, Shean-Shong; Hsieh, Sung-Yuan (Phytotaxa, 2023)
Trichoderma spp. are widely distributed worldwide. Members of Trichoderma have been shown to play a significant role in the biocontrol of plant disease, as well as the industrial production of enzymes and antibiotics, and as a mycoparasite of edible fungi. In this study, a new species, Trichoderma orarium, is introduced and illustrated. This new species was isolated from coastal soil in Northeastern Taiwan and identified based on morphological characteristics and multi-gene sequence analyses of three loci (ITS, tef1, and rpb2). The phylogenetic analyses revealed that T. orarium belongs to the Harzianum clade. Distinctions between the new species and its close relatives are discussed in detail.